2020
DOI: 10.1186/s12879-020-05004-8
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on Xpert MTB/RIF for detection of tuberculosis in a teaching hospital in China

Abstract: Background: The Xpert MTB/RIF assay is an automated molecular test that is designed to simultaneously detect Mycobacterium tuberculosis (MTB) complex and rifampin resistance. However, there are relatively few studies on this method in China. Xpert has been routinely used at Peking University People's Hospital (PKUPH) since November 2016. Thus, the aim of this study was to evaluate the performance of Xpert, and provide a reference and guidance for the detection and diagnosis of TB in non-TB specialized hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Bronchoscopy can be valuable for these patients as it can obtain suitable specimens from the lower respiratory tract while inspecting all the available airways (Mondoni et al, 2017). Literature regarding the diagnostic accuracy of the Xpert assay on bronchoalveolar lavage fluid (BALF) is limited, and most studies have used small sample sizes (Barnard et al, 2015;Fakey Khan et al, 2019;Kilaru et al, 2019;Li et al, 2020;Lu et al, 2018;Pan et al, 2018;Silva et al, 2019;Theron et al, 2013;Theron et al, 2014). Due to this limited research, no formal recommendation for using the Xpert MTB/RIF assay on BAFL exists.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchoscopy can be valuable for these patients as it can obtain suitable specimens from the lower respiratory tract while inspecting all the available airways (Mondoni et al, 2017). Literature regarding the diagnostic accuracy of the Xpert assay on bronchoalveolar lavage fluid (BALF) is limited, and most studies have used small sample sizes (Barnard et al, 2015;Fakey Khan et al, 2019;Kilaru et al, 2019;Li et al, 2020;Lu et al, 2018;Pan et al, 2018;Silva et al, 2019;Theron et al, 2013;Theron et al, 2014). Due to this limited research, no formal recommendation for using the Xpert MTB/RIF assay on BAFL exists.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the detection limit of Xpert is 131 CFU/ml; any unit lower than this value cannot be detected, resulting in negative results. Moreover, although Xpert shows both high sensitivity and specificity, and suggests its high value in PTB diagnosis; however, the application of pleural fluid is still limited, and should be improved [ 28 ]. Therefore, in some special cases, mNGS can be recognized as an important complement to Xpert in tuberculosis diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the WHO endorsed the new-generation Xpert technology, named Xpert MTB/RIF Ultra (Xpert-Ultra), to replace Xpert for HIV patients, children, or EPTB ( Park and Kon, 2021 ). Several studies found that when pleural fluid was used to diagnose TP, the Xpert assay had high specificity (100%) for the diagnosis of TP-related pleural effusion, indicating its value in confirming a TP diagnosis; however, the low sensitivity (14–34%) indicates that the Xpert assay is of limited value for TP screening ( Maynard-Smith et al., 2014 ; Huo and Peng, 2018 ; Li et al., 2020 ). Low sensitivity may be attributed to the presence of Polymerase Chain Reaction (PCR) inhibitors in pleural fluid, or the loading of MTB is too low that the detection limit cannot be reached even by centrifugation ( Huo and Peng, 2018 ).…”
Section: Discussionmentioning
confidence: 99%